From the Epistemological change to the change of practices: the implementation of legal clinics from a constructivist approach in Argentina - H. E. Ruiz (Universitat Politècnica de València, 2016)
Law schools as professional training institutions of central importance in the life of a society, must give not just a formal relevance but real importance to teaching methods that promote a type of deep and motivating learning, allowing to the students the apprehension of values of justice, equity, equality and democracy. This paper discuss the need for a change in the epistemological perspective: a shift from a positivist view towards a constructivist approach of learning as a way to deal with the serious training deficiencies detected. It is necessary to modify the traditional curricular organization, based on the epistemological and traditional concept of teaching, resulting in a lack of connection as well as no relationship between the knowledge imparted. But it is not enough altering the curriculum subjects or the order of the contents, it is necessary to modify the conception of knowledge which presides over the organization of content and teaching practices. In this sense, the real learning contexts developed by community services as an university activity -particularly through legal clinics- allows apprehension of a sort of meaningful knowledge, possibly would be the solution. Because we support the idea that the learnings should be operated from the social practices, to the production of knowledge, which helps to achieve a true integration of the three functions ascribed to Modern Universities: Teaching-Research-Extension.